Marketing Problems of Potato Farmers in Munshigonj District of Bangladesh - Jahan, Sifat; Hossain, Mohammad Abul; Habib, Md Ahsan; Rimi, Shamima Akter; Islam, Md Saiful (Research in Agriculture Livestock and Fisheries, 2021)
The study was conducted in the Lohajang upazilla under Munshigonj district. The main purposes of the study were i) to describe the selected characteristics of the potato farmers; ii). to determine the extent of marketing problems faced by the farmers and iii). to explore relationship between selected characteristics of the farmers and their marketing problems. From the findings it was revealed that about one half of the respondents were middle aged and another half was young (41.9%) and old (8.6%). The highest proportion (73.3%) achieved education ranging from primary to above secondary. Rest of the respondents had no school education. All the respondents had organizational participation. More than two third had medium to high organizational participation. Potato growers of Lohajang were not so much financially sound as the result showed that only (6.7 %) had high capability and the overwhelming majority (58.1% & 35.2%) were under low to medium category. Regarding knowledge, one half of the respondents had low knowledge and the other half had medium to high knowledge. Distance of market place showed not much problems because (81%) of the respondents stayed within 2 km of market place. Among the respondents, the highest (52.4%) proportion had medium storage facilities, while (23.8 %) potato growers had low and high storage facilities. Among the respondents the highest (49.5 %) potato growers faced medium problem in potato marketing. Regarding the relationship between the selected dependent and independent variable, it was observed that age and distance of market place had significant positive relationships with marketing problems of potato growers. Educational level, financial capabilities, extent of use of quality control, availability of marketing information and storage facilities had significant negative relationships with marketing problems of potato growers. On the other hand, organizational participation had no relationship with marketing problems of potato growers. Res. Agric., Livest. Fish.8(1): 33-40, April 2021